Minimizing an Electron Flow to Molecular Oxygen in Photosynthetic Electron Transfer Chain: An Evolutionary View - Kozuleva, Marina A.; Ivanov, Boris N.; Vetoshkina, Daria V.; Borisova-Mubarakshina, Maria M. (Frontiers in Plant Science, 2020)
Recruitment of H2O as the final donor of electrons for light-governed reactions in photosynthesis has been an utmost breakthrough, bursting the evolution of life and leading to the accumulation of O2 molecules in the atmosphere. O2 molecule has a great potential to accept electrons from the components of the photosynthetic electron transfer chain (PETC) (so-called the Mehler reaction). Here we overview the Mehler reaction mechanisms, specifying the changes in the structure of the PETC of oxygenic phototrophs that probably had occurred as the result of evolutionary pressure to minimize the electron flow to O2. These changes are warranted by the fact that the efficient electron flow to O2 would decrease the quantum yield of photosynthesis. Moreover, the reduction of O2 leads to the formation of reactive oxygen species (ROS), namely, the superoxide anion radical and hydrogen peroxide, which cause oxidative stress to plant cells if they are accumulated at a significant amount. From another side, hydrogen peroxide acts as a signaling molecule. We particularly zoom in into the role of photosystem I (PSI) and the plastoquinone (PQ) pool in the Mehler reaction.